1999
DOI: 10.4098/at.arch.99-7
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the European hare. 54. Relationship between density of brown hare Lepus europaeus and landscape structure in Poland in the years 1981-1995

Abstract: Relationships between density of brown hare Lepus europaeusand landscape structure in Poland in the years 1981-1995 Marek PANEK and Robert KAMIENIARZ Panek M. and Kamieniarz R. 1999. Relationships between density of brown hare Lepus europaeus and landscape structure in Poland in the years 1981-1995. Acta Theriologica 44: 67-75.The relationships between the density of brown hare Lepus europaeus Pallas, 1778 and landscape structure were analysed on the basis of data collected for 11 study areas between 1991 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
60
0
1

Year Published

2001
2001
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(63 citation statements)
references
References 10 publications
2
60
0
1
Order By: Relevance
“…In line with this, several studies have indicated that the positive effects of farming for European hares decreased as field size increased and habitat diversity decreased (Schröpfer and Nyenhuis 1982;Tapper and Barnes 1986;Lewandowski and Nowakowski 1993;Panek and Kamieniarz 1999;Vaughan et al 2003;Jennings et al 2006). Habitat diver- (Marboutin and Aebischer 1996) is restricted: The alternative feeding sites for hares in summer might be far away and could act as hot spots for numerous other hares facing the same fate, resulting in potential risks of social stress (Lindlöf 1978;Monaghan and Metcalfe 1985), disease transmission and malnutrition (Tapper and Barnes 1986;Onderscheka 1996).…”
Section: Conclusion For Habitat Managementmentioning
confidence: 83%
“…In line with this, several studies have indicated that the positive effects of farming for European hares decreased as field size increased and habitat diversity decreased (Schröpfer and Nyenhuis 1982;Tapper and Barnes 1986;Lewandowski and Nowakowski 1993;Panek and Kamieniarz 1999;Vaughan et al 2003;Jennings et al 2006). Habitat diver- (Marboutin and Aebischer 1996) is restricted: The alternative feeding sites for hares in summer might be far away and could act as hot spots for numerous other hares facing the same fate, resulting in potential risks of social stress (Lindlöf 1978;Monaghan and Metcalfe 1985), disease transmission and malnutrition (Tapper and Barnes 1986;Onderscheka 1996).…”
Section: Conclusion For Habitat Managementmentioning
confidence: 83%
“…According to optimal foraging theory, animals select foods that maximize their net rate of energy gain [52,54]. When making foraging decisions, such as the selection of food patches, a vulnerable herbivore like the hare needs to evaluate not only the potential benefits (energy gains), but also the costs (elevated predation risk) of any action [52,[55][56][57]. The observed differences in the diet diversity indices among herbivores can be attributed to the dominance of shrubs and grasses in the diets of goats and hares respectively.…”
Section: Discussionmentioning
confidence: 99%
“…They were less common on pastural farms. Panek and Kamieniarz (1999) found the density of the European brown hare in different landscape areas of Poland between 1981-1995 to be ranging from 0.07 to 5.18 ind/km 2 (hunting bag). Strauss and Pohlmeyer (2001) recorded the greatest abundancies with 24.8-27.6 hares/km 2 during years 1995-1999 in the county of Wesermarsch (Lower Saxony, Germany) which is quite comparable to our study.…”
Section: Distribution Of the European Brown Hare In Relation To Variomentioning
confidence: 99%